Optimal fiscal policy and sovereign debt crises - Stefan Niemann; Paul Pichler (Oesterreichische Nationalbank (OeNB), 2017)
This paper studies how sovereign risk – both fundamental and self-fulfilling – shapes the cyclical behavior of optimalfiscal policy. We develop a model with endogenous default costs where market sentiment can induce belief-driven debt rollover crises. Optimal taxes and public spending are generally procyclical, but the incidence of rollover risk gives rise to infrequent episodes of severely countercyclicaliscal activity. These endogenous regime changes are associated with pronounced countercyclical changes in the level of debt. Debt buildups are triggered already by relatively mild recessions, but successful fiscal consolidations occur only in exceptionally good times.
Keywords: E62; F34; H63; 330; Fiscal policy; sovereign debt; rollover crises; regime switches